2020
DOI: 10.1364/ao.397559
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effect of LED nonlinearity on the performance of layered ACO-OFDM

Abstract: Visible light communication (VLC) depends on light emitting diodes (LEDs) for data transmission. This is one of the strengths of VLC motivated by high optical efficiency and low cost. However, LEDs impose nonlinear effects on the transmitted signal and limit overall system performance, especially in the case of multicarrier modulation systems. This paper extends to the layered asymmetrically clipped optical, orthogonal frequency division multiplexing (LACO-OFDM) and investigates the impact of LED nonlinearity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Because of their high peak power, LED chips are susceptible to overheating. Consequently, the high PAPR of the OFDM signal should be reduced until it is fed into the transmitter LEDs before it is sent [31,32].…”
Section: Severalmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their high peak power, LED chips are susceptible to overheating. Consequently, the high PAPR of the OFDM signal should be reduced until it is fed into the transmitter LEDs before it is sent [31,32].…”
Section: Severalmentioning
confidence: 99%
“…A photodiode (PD) detects the optical signal and transforms it into an electrical signal at the receiver. According to [45], At the receiver, a PD detects the optical signal and transforms it into an electrical signal. According to [45], when translated to the frequency domain, negative clipping distortion occurs exclusively on even subcarriers, and it is orthogonal to the transmitted data on odd subcarriers.…”
Section: Formentioning
confidence: 99%
“…An incorporating sphere with an internal part covered with Spectralon and a parameter used to measure the spectrofluorometer was used to assess the quantum efficacy (QE) (Horiba Jobin-Yvon Fluorolog 3-22 Tau-3). Liu et al [9] have demonstrated earlier the measuring methodologies and correlating theory [10]- [12]. A hue analyst called Laiko DT-100 along with its CCD detector was used to determine the commission international de i'eclairage or briefly called CIEchromatic coordinates applied in every specimen.…”
Section: Experimental Details 21 Characterization Of the Ca3si2o4n2:e...mentioning
confidence: 99%
“…Sharafat described the crystal composition of Ca3 subsequently. The Ca3-xSi2O4+2xN2-2x [10], [11] The enhancement of the dual-layer phosphorus configuration in color uniformity … (Phuc Dang Huu) 767 phosphors in the manufacture of a wLED using a near-ultraviolet (n-UV) LED are all discussed in this paper. The findings reveal that Ca3Si2 is thermally stable, and white LEDs made by Ca3Si2O4N2:Eu 2+ obtain great CRI [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…Employing yellow YAG:Ce phosphorus, red InP-based QDs, and green Sr0.94Al2:Eu0.06 phosphorus, Kwon et al [17] earned good CRI of WLED. Lecca et al [18] and Elkarim et al [19] created a WLED comprising green, red CdSe/ZnS core-cover QDs and an InGaN/GaN blueemitted light.…”
mentioning
confidence: 99%